2017
DOI: 10.2209/tdcpublication.2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effect of Oral Premedication with Ibuprofen or Dexamethasone on Anesthetic Efficacy of Inferior Alveolar Nerve Block in Patients with Irreversible Pulpitis: A Prospective, Randomized, Controlled, Double-blind Study

Abstract: The purpose of this prospective, randomized, double-blind, placebo-controlled study was to determine the effect of preoperative oral administration of ibuprofen or dexamethasone on the success rate of inferior alveolar nerve block (IANB) in patients with symptomatic irreversible pulpitis. Seventy-eight patients with irreversible pulpitis were randomly divided into 3 groups (26 per group) and given one of the following at 1 hr prior to performing local anesthesia: a placebo; 400 mg ibuprofen; or 4 mg dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 23 publications
0
34
2
Order By: Relevance
“…Aggarwal et al (2021) reported an anaesthesia success rate of 73% with intraligamentary dexamethasone injection applied in addition to standard IANBs using lidocaine in mandibular molars with SIP. Bidar et al (2017) registered a success rate of 80.8% using a pre-operative oral dose of 4 mg dexamethasone, which increased the pulpal anaesthesia success rate significantly in comparison to the control group. In the present study, with the pre-operative submucosal use of 8 mg dexamethasone, the pulpal anaesthesia success rate (47%) was higher than the control group (37%) and lower than the tramadol (57%) and articaine (63%) groups.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Aggarwal et al (2021) reported an anaesthesia success rate of 73% with intraligamentary dexamethasone injection applied in addition to standard IANBs using lidocaine in mandibular molars with SIP. Bidar et al (2017) registered a success rate of 80.8% using a pre-operative oral dose of 4 mg dexamethasone, which increased the pulpal anaesthesia success rate significantly in comparison to the control group. In the present study, with the pre-operative submucosal use of 8 mg dexamethasone, the pulpal anaesthesia success rate (47%) was higher than the control group (37%) and lower than the tramadol (57%) and articaine (63%) groups.…”
Section: Discussionmentioning
confidence: 84%
“…One of the methods used for increasing pulpal anaesthetic effectiveness is submucosal injection that is administered to the buccal of the affected tooth (Aksoy & Ege, 2020b;Isiordia-Espinoza et al, 2012). This study investigated the effectiveness of pre-operative articaine (whose anaesthetic activity is well-known), tramadol (Ege et al, 2018) and dexamethasone (Bidar et al, 2017;Shahi et al, 2013), which are generally used for post-operative pain management but have recently been reported to increase the anaesthetic activity of standard IANBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is apparent from these studies that no matter which type of medication is used, standardization with respect to dosage as well as initial diagnosis is essential in these types of studies to obtain more reliable results. A recent study also compared the use of ibuprofen with dexamethasone and concluded that both medications increased the success rate of IANB; however there were no significant differences between the two [67]. Their findings on the success of ibuprofen were contradictory to those reported by Aggarwal et al [37], Oleson et al [44], and Shahi et al [31] where ibuprofen was found to have no significant effect.…”
Section: Discussionmentioning
confidence: 98%
“…Literature suggests and advocates for multiple visits so as to reduce the microbes in the canal much as there is no statistical significance in the number of visits [3,5]. Pain and flare-up occurs post-operatively warranting the use of analgesics pre-operatively in some cases such as ibuprofen and at times dexamethasone post-operatively [6]. Moreover, pain being a subjective phenomenon occurs post-operatively after instrumentation regardless of whether it was done in a single or multiple sitting.…”
Section: Introductionmentioning
confidence: 99%